Determinants of Financial Performance and Its Impact on Firm Value: (Study Conducted in Consumer Non-Cyclical Sector Companies Listed on the Indonesia Stock Exchange) - Mulyadi; Humaira Dinda Mulyadi (Accounting and Finance Studies, 2022)
This study aims to examine the determinants of financial performance of Manufacturing Companies In The Consumer Goods Industry during 2014-2020 listed on the Indonesia Stock Exchange (IDX) and their effect on firm value. The factors used in this study consist of Liquidity, Leverage, Risk, and Tangibility of Assets (TOA). Also, profitability is also used as a mediating variable. Firm value is proxied by Price Book Value (PBV). The sampling technique was carried out by purposive sampling method. The research method used is a quantitative method with secondary data. The analysis technique used is Partial Least Square Path Modeling with WarpPLS 7.0 Program. The results showed that Liquidity, Leverage, Risk, and Tangibility of Assets (TOA) has no significant effect on Firm Value. Profitability has significant positive effect on Firm Value. Meanwhile, Profitability succeeded in mediating all the effects of Liquidity, Leverage, Risk, and Tangibility of Assets (TOA) on Firm Value. For future researchers, it is expected to use Firm Value proxies outside of this study, research object outside of the population that have been studied, and extend the research period. Further researchers are expected to be able to use other models and add other variables beyond those already used in this study.